Reactive extraction of pyruvic acid using mixed extractants. Issue 7 (2nd May 2016) - Pal, Dharm; Thakre, Niraj; Kumar, Awanish; Keshav, Amit
ABSTRACT: The synergistic effect of mixing of extractants (tri- n -butylphosphate, TBP; tri- n -octylamine, TOA; and Aliquat 336, A336) was investigated in view of recovery of pyruvic acid from fermentation media. Extraction experiments were performed at T = 302 K, from aqueous solution of pyruvic acid (0.025–0.2 kmol m −3 ) using single and mixed extractants in decanol. Parameters such as distribution coefficient, K D ; equilibrium constant, K eq ; and extraction efficiency, E % were used to analyse the results. Equilibrium constants, K eq, were evaluated to be 15.376 m 3 kmol −1, 9.242 m 3 kmol −1, and 0.0778 m 3 kmol −1 for (TBP + TOA), (A336 + TOA) and (TBP + A336), respectively. No overloading ( Z < 0.5) was observed and only a (1:1) complex was proposed. E% were in the order of (TBP + TOA) > (A336 + TOA) > (TBP + A336).